Constitutional Interpretation - Quiroga León, Aníbal (1985)
This article discusses the need and relevance of constitutional interpretation in modern legal systems, emphasizing that the Constitution, in besides being a legal norm, is a political norm that contains fundamental principles for the organization of the Nation. The author criticizes traditional hermeneutics, considering it insufficient to capture the changing dynamics of constitutional reality.  He argues that, as society evolves, the methods of interpretation must adapt, recognizing that the constitutional text has an inherent ambiguity that requires a flexible interpretative approach. Along these lines, he points out that the Constitutional Court plays a crucial role in interpretative work, ensuring that decisions are not based solely on a literal adherence to the law, but on an appreciation of constitutional values and principles. The article also stresses that interpretation must be a concrete determination, adapted to each case, which implies an interaction between the norm and reality. Finally, it is emphasized that constitutional interpretation has clear limits: respect for the normative text and legislative intention; avoiding any attempt at constitutional reform through interpretation, which in turn contributes to the strengthening of democracy and the maintenance of the unity of the legal system.